Novel and Innovative Techniques in Phytopharmaceutical Formulations and Nano-Metallic Medicine (AYUSHDHARA, 2025)
Phytopharmaceuticals have long been a cornerstone of traditional medicine, valued for their natural origin, therapeutic efficacy, and minimal side effects. With growing scientific interest and technological advancements, these natural remedies are being re-engineered using modern tools such as nanotechnology. This article explores the paradigm shift occurring in herbal drug formulations, particularly the application of novel drug delivery systems like liposomes, phytosomes, and nanoparticles to improve bioavailability and therapeutic targeting. The synthesis of nano-metallic Ayurvedic medicines is also discussed, revealing how ancient knowledge is merging with modern pharmacology to yield promising solutions for complex diseases like cancer, neurodegeneration, cardiovascular disorders, and gastrointestinal diseases. The article presents an integrated view of phytopharmaceutical innovation with scientific rigour and Ayurvedic wisdom, urging further clinical studies and standardization protocols for global acceptance.